Personal Branding of Three Female Bureaucrats with A Feminist Stylistics Approach - Widarwati, Nunun Tri; Putra, Ardian Prima (UNIB Press, 2024)
This study attempts to measure Personal Branding of Three Female Bureaucrats : A Feminist Stylistics Approach. This study adopted a qualitative method. Data gathered through a several documents from social media. Findings of the study indicate that the aforementioned analysis, Sri Mulyani, Retno Marsudi and Denni Puspa Purbasari do have a strong personal branding. They present the image of people who are intelligent and competent in their area, but who nevertheless remain humble and can adapt to any circumstances. When viewed through the lens of Motion personal branding concepts, the three female bureaucrats met most of these criteria: historical narrative, positioning, commodification, aestheticization, moral career, and linguistic realization. They are able to use media as a means of branding, and build a positive reputation. The success of this personal branding can also be proven by the public's response to Sri Mulyani, Retno Marsudi and Denni Puspa Purbasari image and persona, which demonstrate respect and admiration for their figure. The Beneficial of this study are for developing knowledgement of personal branding and translation.